Governance Disclosure Practices of Corporate Sector - Gupta, Meenu (Gyan Management Journal, 2015)
The issue of corporate governance continues to receive a high level of attention. Corporate governance  is like a blood which fills the veins of corporate disclosure in form of transparency. The recent global  events concerning high profile corporate failures have put banks in the debate on the efficiency of  corporate governance mechanisms as a means of increasing firm's performance. This paper makes the  comparison regarding corporate disclosure practices in top ten private companies for the year 2003- 04 with 2013-14. It also includes the broad view of corporate governance in India. The study uses  secondary sources of data and finds the differences in the ranking of the companies as per highest  market capitalization and governance practices followed by them. The results indicate that there has  been improvement of disclosure practices in corporate sector over the years
Keywords: Corporate Governance; Disclosure practices; Private companies